Reflections on the margins of the philosophical translation of Luigi Pareyson's Aesthetics in Spanish: between formativity, improvisation and system. (Itinera, 2015)
The here discussed topic was inspired by the work of translation to Spanish (Xorki, 2014) of Luigi Pareyson’s Estetica. Teoria della formatività (Edizioni di Filosofia, 1954). The paper offers a reflection on the way in which improvisation, formativity, and system have played a role in the translation work. The main idea is the essentiality of congeniality for the activity of translation: only if you have captured the spirit and the sense of the text, having penetrated its sense, you are able to translate it to another language. In the case of philosophical translation, the translation of philosophical terms and, to a greater extent, of philosophical metaphors, requires a phase of understanding that goes beyond the understanding of the linguistics components and requires also an authentic interpretation of the meaning of the text. In a second phase, terms which have been chosen initially may not collect all the not dispensable nuances of the original: this is time then for improvisation, i.e., for “testing” and “trying” with terms that at first may not be the most logical and that however “work”, offering in the new edition of the book the nuance and meaning that are closer to the original text. I indicate several examples to illustrate this procedure: “spunto”, “tentare”, “riuscita”, “irrigidire”. The re-reading of the work after the election of such terms, shows whether the new text conveys the philosophical content and style of the original one as well as its systematic nature.